Magical beasts and unbelievable monsters illustrated by Victoria de Larrea. - Woods, Geraldine; Woods, Harold; De Larrea, Victoria (St. Paul, Minn. EMC Pub., 1980)
Discusses the dragon, unicorn, phoenix, kraken, roc, griffon, Sasquatch, Yeti, Loch Ness monster, and other mysterious beasts.
"Special edition."
Keywords: Animals, Mythical -- Juvenile literature; Monsters -- Juvenile literature; Animals, Mythical; Monsters